THE EFFECTIVENESS OF ONLINE EDUCATION FOR STUDENTS TODAY - Juramurodova Guloyim Baxtiyor qizi, Mahanova Muhayyo Nabiyevna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article talks about the online education system, which is very useful for students, especially in language learning, because students prefer online education to offline courses. You can get more detailed information in the article.